The Golgi Apparatus Maintains Its Organization Independent of the Endoplasmic Reticulum - Pecot, Matthew Y. (The American Society for Cell Biology, 2006)
Under artificial conditions Golgi enzymes have the capacity to rapidly accumulate in the endoplasmic reticulum (ER). These observations prompted the idea that Golgi enzymes constitutively recycle through the ER. We have tested this hypothesis under physiological conditions through use of a procedure that captures Golgi enzymes in the ER. In the presence of rapamycin, which induces a tight association between FKBP (FK506-binding protein) and FRAP (FKBP-rapamycin–associated protein), an FKBP-tagged Golgi enzyme can be trapped when it visits the ER by an ER-retained protein fused to FRAP. We find that although FKBP-ERGIC-53 of the ER-Golgi intermediate compartment (ERGIC) rapidly cycles through the ER (30 min), FKBP-Golgi enzyme chimeras remain stably associated with Golgi membranes. We also demonstrate that Golgi dispersion upon nocodazole treatment mainly occurs through a mechanism that does not involve the recycling of Golgi membranes through the ER. Our findings suggest that the Golgi apparatus, as defined by its collection of resident enzymes, exists independent of the ER.